Automated Deduction in Geometry 7th International Workshop, ADG 2008, Shanghai, China, September 22-24, 2008. Revised Papers - Sturm, Thomas; Zengler, Christoph (Springer eBooks., 2011)
This book constitutes the thoroughly refereed post-workshop proceedings of the 7th International Workshop on Automated Deduction in Geometry, ADG 2008, held in Shanghai, China in September 2008. The 11 revised full papers presented were carefully reviewed and selected from numerous initial submissions for the workshop during two rounds of reviewing and improvement. The papers show the lively variety of topics and methods and the current applicability of automated deduction in geometry to different branches of mathematics such as discrete mathematics, combinatorics, and numerics; symbolic and numeric methods for geometric computation, and geometric constraint solving. Further issues are the design and implementation of geometry software, special-purpose tools, automated theorem provers - in short applications of ADG to mechanics, geometric modeling, CAGD/CAD, computer vision, robotics and education.